METHODS OF COLLECTION, PRESERVATION AND FORWARDING OF BIOLOGICAL MATERIAL FOR DNA FINGERPRINTING (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
DNA Fingerprinting technique, introduced by Prof. Alec Jeffrey's is widely used presently all over the globe especially for forensic purposes. All living things are composed of different cells and within the cells except red blood cells and few other minor types contain a chemical component called Nucleus. And within the nucleus of each cell is located a genetic material, referred as Deoxyribonucleic Acid (DNA). It is this genetic material which generates genetic pattern of an individual and has shown highly polymorphic among individuals.
Keywords: utilized; individual